Analysis of Income from Broiler Chicken Businesses Under A Partnership Model in the Temu Village (Case Study of the Livestock Business Owned By Mr. Erwin pah): (Case Study of the Livestock Business Owned By Mr. Erwin pah) - Samsul Arip Umbu Kaboka Jangi; Iven Patu Sirappa; Anggreni Madik Linda (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
This study aims to analyze the income of Mr. Erwin Pah's broiler chicken farming business, which operates under a core-plasma partnership model in Temu Village, Kanatang Subdistrict, East Sumba Regency. The research was conducted using a case study method with primary and secondary data collected during one year of operation with four production cycles. Data analysis included calculations of production costs, receipts, income, and financial feasibility analysis using the B/C and R/C ratios. The results showed that the total revenue for the business during one year was IDR 845,919,250 with total production costs of IDR 1,032,231,703, resulting in a net income of IDR -186,312,453. The B/C Ratio value of 0.82 and the R/C Ratio of –0.18 indicate that the business has not yet achieved financial feasibility in its first year of operation. This negative income is influenced by the dominance of initial investment costs, the number of production cycles that are not yet optimal, and the technical experience of farmers who are still adaptive in the early stages of the business. However, this condition does not reflect the failure of the partnership model, but rather shows the characteristics of the early phase of business development. With increased technical efficiency, optimization of the number of production cycles, and more intensive managerial assistance, the broiler chicken farming partnership business has the potential to achieve financial feasibility and business sustainability in the next period.